MINAT MASYARAKAT DESA LUBUK MUDA KECAMATAN SIAK KECIL KABUPATEN BENGKALIS TERHADAP PEMANFAATAN NIRA NIPAH (Nypa fruticansWurmb.) SEBAGAIBAHAN BAKU BIOETANOL UNTUK ALTERNATIF BAHAN BAKAR - Arta Pansiska T; Defri Yoza; M. Mardhiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Nypa fruticans is the raw material for the manufacture of bioethanol. Bioethanol is a biofuel as an alternative fuel is currently used. Indonesia has a lot of Nypa fruticans plant as raw material but is not yet known how the public interest in utilizing Nypa fruticans sap as a raw material of bioethanol. This research was conducted in the Lubuk Muda Village Siak Kecil District Bengkalis Regency on November 2014-December 2015. The purpose of this research was to determine the public interest village of Lubuk Muda in the use of Nypa fruticans sap as a raw material for alternative fuel bioethanol and identifying the use of Nypa fruticans by Lubuk Muda Village Siak Kecil District Bengkalis Regency. The research result showed that the interests influenced the knowledge, ability, awareness, willingness and motives. Public interest Lubuk Muda Village Siak Kecil District Bengkalis Regency in the use of Nypa fruticans sap classified in the medium category with a percentage 63.3% with the number of respondets as many as 62 people. Nypa fruticans plant utilization by the Lubuk Muda Village Siak Kecil District Bengkalis Regency is part of the leaf to the roof of the house, while shoots leaves are used for wrapping cigarettes, section palm fruit is consumed by way of direct edible and use as syrup. As well as direct drink Nypa fruticans sap, made wine and processed into bioethanol as an alternative fuel. Keywords: interest, sap, Nypa fruticans, bioethanol